Utilization Of Bentonite as A Substitute for Filler in Asphalt Concrete-Binder Course (AC-BC) - Pratama, Tegar Wahyu; Azwansyah, Heri; Mayuni, Siti (Jurnal Teknik Sipil, 2024)
Bentonite is a term used in the trade industry to refer to clays that contain montmorillonite and belong to the dioctahedral group. Bentonite possesses unique properties, such as expanding when mixed with water. This property of bentonite is expected to enhance the performance of asphalt mixtures, particularly in the Asphalt Concrete-Binder Course (AC-BC). This research aims to analyze the Marshall characteristics, calculate the Optimum Asphalt Content (OAC) values, assess the layer performance, and determine the optimal percentage of substitution content in the Asphalt Concrete-Binder Course (AC-BC) layer. The research was conducted in several stages. The first stage involved testing the characteristics of the materials. In the second stage, test specimens were prepared with different known asphalt content variations. The third stage involved performing Marshall tests. The fourth stage analyzed the Marshall characteristics using the Bina Marga 2018 Revision 2 method. In the fifth stage, the OAC values were calculated for each variation of the asphalt mixture. The sixth and final stage involved drawing conclusions based on the previous stages. The Marshall test results for the Marshall characteristics determined the OAC for each variation: 6.20%, 6.25%, 6.10%, and 5.95%. Using bentonite in asphalt mixtures can improve stability across different bentonite content variations. With each addition of bentonite, the Voids in Mineral Aggregate (VIM) value is affected, as the VIM value decreases with increased bentonite usage. This suggests that bentonite fills the voids in the asphalt mixture. A lower VIM value indicates a more rigid asphalt mixture with each addition of bentonite and asphalt content.Keywords:  Bentonite in asphalt mixtures, Swelling properties of bentonite, Marshall characteristics in AC-BC, Optimum Asphalt Content (OAC) value, Bentonite substitution in pavement layers.